2015
DOI: 10.1063/1.4922272
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity in undoped hafnium oxide

Abstract: We report the observation of ferroelectric characteristics in undoped hafnium oxide thin films in a thickness range of 4–20 nm. The undoped films were fabricated using atomic layer deposition (ALD) and embedded into titanium nitride based metal-insulator-metal (MIM) capacitors for electrical evaluation. Structural as well as electrical evidence for the appearance of a ferroelectric phase in pure hafnium oxide was collected with respect to film thickness and thermal budget applied during titanium nitride electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
255
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(278 citation statements)
references
References 32 publications
14
255
1
3
Order By: Relevance
“…12,[21][22][23] It is widely recognized that the ferroelectricity in HfO 2 is attainable in a particular range of dopant concentrations, and its spontaneous polarization is induced by the displacement of oxygen ions in the noncenter symmetric orthorhombic phase crystal. 1,4,5) The ferroelectricity of HfO 2 films is maximized in ultrathin films of around 10 nm thickness.…”
Section: Introductionmentioning
confidence: 99%
“…12,[21][22][23] It is widely recognized that the ferroelectricity in HfO 2 is attainable in a particular range of dopant concentrations, and its spontaneous polarization is induced by the displacement of oxygen ions in the noncenter symmetric orthorhombic phase crystal. 1,4,5) The ferroelectricity of HfO 2 films is maximized in ultrathin films of around 10 nm thickness.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, hafnium dioxide (HfO 2 ) based insulators have emerged as the primary contenders to replace traditional SiO 2 in a variety of nano-electronic devices ranging from deep-scaled transistors to DRAM 1,2 and non-volatile memory cells. 3,4 Furthermore, thanks to the ferroelectricity property of both doped 5,6 and pure 7 HfO 2 , novel applications including memories 8 and high sub-threshold slope transistors 9 are envisioned. However, the reliability of the dielectric associated with electron trapping appears to be the "show stopper": It has already been shown that the positive bias-temperature instability (PBTI) limits the gate oxide scaling in metal-HfO 2 -Si transistors [10][11][12][13] while in flash cells, electron trapping in the intergate HfO 2 insulator degrades the program/erase window, retention, and endurance.…”
mentioning
confidence: 99%
“…Additional relaxations in atomic positions and cell shape follow in order to relieve strain, to the extent allowed by the symmetry of the ordered oxygen ion/vacancy arrangement, yet those additional relaxations are much smaller than the initial oxygen ion displacements to the sites of the Pbcm lattice. 2 The resulting hierarchy of structures is illustrated in Fig. 2d.…”
mentioning
confidence: 99%
“…The interest in metastable hafnia (HfO 2 ) and zirconia (ZrO 2 ) phases has been intensified with the recent reports of ferroelectric and antiferroelectric responses in "doped" (alloyed) and some pure (Zr,Hf)O 2 films [1,2]. This discovery is of great interest to the semiconductor industry and has led to intensive experimental [3][4][5][6][7][8][9][10][11][12][13][14] and theoretical [9,[15][16][17][18][19][20][21][22] research, because these materials are believed to avoid the problems typical for the traditional ferroelectric materials (such as lead zirconate titanate) during integration into microelectronic devices.…”
mentioning
confidence: 99%
See 1 more Smart Citation